Prognostic value of plasma B-type natriuretic peptide levels after exercise in patients with severe asymptomatic aortic stenosis. Issue 20 (3rd July 2014) - Capoulade, Romain; Magne, Julien; Dulgheru, Raluca; Hachicha, Zeineb; Dumesnil, Jean G; O'Connor, Kim; Arsenault, Marie; Bergeron, Sébastien; Pierard, Luc A; Lancellotti, Patrizio; Pibarot, Philippe
Abstract : Background: Exercise-stress echocardiography is useful in management and risk stratification of patients with asymptomatic aortic stenosis (AS). Resting B-type natriuretic peptide (BNP) level is associated with increased risk of adverse events. The incremental prognostic value of BNP response during exercise is unknown. Objective: The purpose of this study was to assess the usefulness of plasma level of BNP during exercise to predict occurrence of events in asymptomatic patients with severe AS. Methods: Resting and exercise-stress echocardiographic data and plasma BNP levels were prospectively collected in 211 asymptomatic AS patients in whom 157 had severe AS with preserved LVEF in two centres. The study end-point was the occurrence of death or aortic valve replacement. Results: Plasma BNP level increased from rest to exercise (p<0.0001). During a mean follow-up of 1.5±1.2 years, 87 patients with severe AS reached the predefined end-point. Higher peak-exercise BNP level was associated with higher occurrence of adverse events (p<0.0001). In multivariate analysis, second and third tertiles of peak-exercise BNP (T2: HR=2.9; p=0.002 and T3: HR=5.3; p<0.0001, respectively) were powerful predictors of events compared with the first tertile. Further adjustment for resting BNP provided comparable results (T2: HR=2.8; p=0.003 and T3: HR=5.0; p<0.0001). This relationship persisted in both subsets of patients with low or high resting BNP. Conclusions: This study reports that peak-exercise BNP level provides significant incremental prognostic value beyond what is achieved by demographic and echocardiographic data, as well as resting BNP level.